Reinforcement of steel beam-to-double column moment connection using side plates - Yousef Zandi; Afram Keivani (Civil and Sustainable Urban Engineering, 2021)
One of the disadvantages of conventional steel structures in Iran is the common way of I-shaped beam to double column fixed connection that do not perform well against seismic loads. This article uses the side plate to modify and optimize the connection. Using this new geometry, the beam-to-column direct connection is eliminated, and there is no longer any concern about the brittle fracture of penetration weld of the beam-to-column connection and the weakness of panel zone that occur in the common fixed connections. In addition, by eliminating the direct transfer of beam flange force to the double column connection plate, the problem of deformation, complexity or buckling of the cover plate of the column is spontaneously removed. In this paper, in order to investigate the nonlinear behavior of beam-to-double column connection system, a number of three-dimensional finite element models under the effect of cyclic loading have been analyzed. The results show that the beam-to-double column connection using the side plates has good strength and ductility and can be used in special moment frames for seismic areas.